NILAI GLUKOSA DARAH DAN TOTAL PROTEIN PLASMA PADA SAPI SIMPO YANG MENDERITA TREMATODIASIS DI PETERNAKAN RAKYAT DESA LABUHAN RATU KABUPATEN LAMPUNG TIMUR - Ilda Rina Sandria, Madi Hartono, Sri Suharyati, dan Purnama Edy Santosa (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2019)
The research aims to determine the value of blood glucose and plasma total protein in Simpo cattle suffering from trematodiasis. The research was conducted in December 2018 by taking blood samples of Simpo cattle in East Lampung. The research design used Completely Randomized Design (CRD) with 3 treatments and 4 replications from Simpo cow blood samples. The treatment used is P0: Simpo cattle which are not infested by worms; P1: Simpo cattle infested with 1 type of worm; and P2: Simpo cattle infested with 2 types of worms. Blood glucose value were analyzed in Biolab Indonesia Partner and total plasma were analyzed at Lampung Veterinary Center. Data from the observations were analyze using variance at the real level (P <0,10) and continued with the Small Significant Difference test. The results of this study showed that Simpo cattle suffering from trematodiasis had significant effected (P <0,10) on blood glucose values and had no significant effected (P> 0,10) on total plasma protein. The highest number of blood glucose values at P0(65,00 mg / dL) and the lowest at P1 (56,75 mg / dL). Total plasma protein at P0 (7,20 g / dL), P1 (7,30 g / dL), and P2 (6,95 g / dL). Key word : Blood glucose, Total plasma protein, Simpo cattle, Trematodiasis, Traditional farmer